Protocol: the American Women: Assessing Risk Epidemiologically (AWARE) cohort study - Rebecca Schnall; Mirjam-Colette Kempf; Gregory Phillips; Jodie A. Dionne; Gina Wingood; Dustin Marsh Long; Robert Klitzman; Tonda L. Hughes; Jianfang Liu; Ariann F. Nassel; Jessica Lee Corcoran; Amy K. Johnson (BMC Public Health)
Abstract Background While progress has been made in reducing HIV incidence rates among cisgender women, it continues to fall short of reaching the goal of ending the HIV epidemic with no new cases. Objective This study aims to use innovative electronic methods (e.g., social media with community-informed advertisements) to recruit and retain a large (N = 1,800), diverse national sample of women at higher risk for HIV seroconversion who are 14 years of age and older to better understand the predictors of HIV-related sexual risk and HIV incidence within the context of a theoretically-grounded social-ecological framework. Methods A US-based national longitudinal cohort study was launched among cisgender women with greater likelihood of HIV seroconversion Participants complete a survey with items related to demographics, substance use, mental health symptoms, interpersonal violence and other social factors. Biospecimens include self-collected vaginal and rectal swabs, and blood in microtainers to test for HIV, syphilis, chlamydia, gonorrhea, and trichomoniasis every 6 months for 2 years. Results Participant recruitment began in June 2023 and baseline enrollment is scheduled to finish in July 2025. Discussion Innovative and culturally sensitive strategies to improve access to HIV prevention and treatment services for cisgender women are vital to curb the burden of the HIV epidemic for this key population. Findings from this study will inform future research, intervention strategies, and public policies.